Global burden of sleep disturbances among older adults and the disparities by geographical regions and pandemic periods - Min Du; Min Liu; Yaping Wang; Chenyuan Qin; Jue Liu (Elsevier, 2024)
Sleep disturbances are highly prevalent during the COVID-19 pandemic, especially among older adults. We aimed to evaluate sleep heath during COVID-19 pandemic and assess the differences among geographical regions and pandemic periods. We searched three databases (PubMed, Embase, Web of Science) to find articles up to March 12, 2023. We included observational studies that reported the prevalence of sleep disturbances among adults aged 60 years or older in any setting. Two researchers independently reviewed the literature and retrieved the data. We used Der Simonian-Laird random effects meta-analyses to pool the data, followed by subgroup analysis, sensitivity analysis, and meta-regression. A total of 64 studies with 181,224 older adults during the pandemic were included. The prevalence of poor sleep quality, short sleep duration, long sleep duration, and insomnia symptoms were 47.12% (95% CI: 25.97%, 68.27%), 40.81% (95% CI: 18.49%, 63.12%), 31.61% (95% CI: 24.83%, 38.38%), and 21.15% (95% CI: 15.30%, 27.00%), respectively. The prevalence of sleep problems reported by self-constructed items was 26.97% (95% CI: 20.73%, 33.22%). When compared to America (64.13%), Europe (20.23%) and the Western Pacific (21.31%) showed a lower prevalence of sleep problems (all P < 0.0001). The prevalence of worsened sleep problems was 27.88% (95% CI: 11.94%, 43.82%). Compared to 2020 (15.14%), it increased to 47.42% in 2021 (P < 0.05). Eight studies on sleep disturbances among 672 older COVID-19 patients were included. The prevalence of sleep problems and insomnia symptoms among older COVID-19 patients were 41.58% (95% CI: 21.97%, 61.20%) and 41.56% (95% CI: 28.11%, 58.02%), respectively. A significant burden related to poor sleep has been observed among older adults worldwide over the past three years, with variations across different regions and time periods. It is important to make more efforts in prevention and intervention to identify the risk factors, treatment, and rehabilitation of sleep disturbances for healthy aging.